Potential Role of the Gut Microbiome In Colorectal Cancer Progression - Kim, Jaeho; Lee, Heung Kyu (Frontiers in Immunology, 2022)
An increasing number of studies have revealed that the progression of colorectal cancer (CRC) is related to gut microbiome composition. Under normal conditions, the gut microbiome acts as a barrier to other pathogens or infections in the intestine and modulates inflammation by affecting the host immune system. These gut microbiota are not only related to the intestinal inflammation associated with tumorigenesis but also modulation of the anti-cancer immune response. Thus, they are associated with tumor progression and anti-cancer treatment efficacy. Studies have shown that the gut microbiota can be used as biomarkers to predict the effect of immunotherapy and improve the efficacy of immunotherapy in treating CRC through modulation. In this review, we discuss the role of the gut microbiome as revealed by recent studies of the growth and progression of CRC along with its synergistic effect with anti-cancer treatment modalities.